TINDAK TUTUR PADA BAHASA PROMOSI (ENDORSEMENT) DI INSTAGRAM - Melisa Sheila; Gallant Karunia Assidik (Universitas Majalengka, 2022)
Various kinds of media are used as a place of promotion today, one of which is Instagram. The contributing factor is the emergence of a large impact which is often called an influencer with diverse speech or speech acts and attracts the attention of the speech partner with their respective promotional language strategies. This study has a purpose, namely (1) finding the form of promotional language speech acts (endorsement) onInstagram (2) describing the forms of promotional language speech acts onInstagram (endorsement). The type of research used The type of research used is qualitative research using descriptive methods in describing the data found. The data from this research is using qualitative data, which is the speech act data of influencers the selected. While the data source is taken from the speech acts of the influencers onInstagram that have been selected. In this study using data collection techniques documentation and observation. Documentation technique is done by listening, reading, and speaking methods. For data validation used theory triangulation. The results of this study indicate that there are (1) 6 data of assertive speech acts (2) 10 data of directive speech acts (3) 4 data of expressive speech acts (4) 10 data of commissive speech acts. In the deepest assertive speech act suggesting, in the directive speech act there is a recommending and commanding speech act, in the expressive speech act there is a praising speech act and a commissive speech act there is an offering commissive speech act. Of speech acts assertive in endorsing there are a number of 6, totaling 10 directive speech acts, expressive speech acts amounted to 4, and the speech act 10.jumlah Komis as many as the entire data totaling 30 types of speech acts that are often used in the promotion of (endorsement) is a follow directive speech and commissive speech acts, can be seen in the table of directive and commissive speech acts, each totaling 10.